Primitive spatial relations based on SKIZ - Jan, SR; Hsueh, YC (My University, 2000)
Spatial relations between objects or regions in an image play important roles in scene understanding. However, it is difficult to define these relations for automation. Most existing methods for defining spatial relations depend on angle measurements between points of the two objects of interest. In this study, we propose a new approach based on the concept of skeleton by zones of influence (SKIZ) for recognizing the primitive spatial relations between objects or regions in a segmented image. The approach is compared with the aggregation and compatibility methods. The experimental result shows the proposed approach is effective and fast. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: spatial relations; aggregation method; compatibility method; skeleton by zones of influence; watershed